2019
DOI: 10.1097/pas.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

Adult Granulosa Cell Tumor With High-grade Transformation

Abstract: Adult granulosa cell tumor (AGCT) is a low-grade malignant neoplasm with a significant propensity for late recurrence and metastasis. Almost all AGCTs are composed of cells with bland nuclear features and even when these tumors recur or metastasize, the nuclear features are almost always low-grade. We report 5 cases of AGCT in patients aged 37 to 88 years composed of areas of typical AGCT with low-grade morphology admixed with areas of high-grade morphology, with marked nuclear atypia, often with bizarre multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…In the literature, cases of AGCTs with areas of high-grade malignant morphology in either the primary tumor or recurrence have been reported. One study detected a TP53 mutation in these high-grade components of 2/4 FOXL2 mutant AGCTs and stated that TP53 mutation likely plays a role in the high-grade transformation [31]. A recent case report describes an aggressive AGCT without a FOXL2 mutation with strongly positive p53 immunohistochemistry and numerous mitoses [32], possibly similar to our finding of one FOXL2-wildtype TP53-mutant AGCT with high mitotic activity.…”
Section: Subgroup Of Patients With High-grade Agct Characterized By Tsupporting
confidence: 86%
See 1 more Smart Citation
“…In the literature, cases of AGCTs with areas of high-grade malignant morphology in either the primary tumor or recurrence have been reported. One study detected a TP53 mutation in these high-grade components of 2/4 FOXL2 mutant AGCTs and stated that TP53 mutation likely plays a role in the high-grade transformation [31]. A recent case report describes an aggressive AGCT without a FOXL2 mutation with strongly positive p53 immunohistochemistry and numerous mitoses [32], possibly similar to our finding of one FOXL2-wildtype TP53-mutant AGCT with high mitotic activity.…”
Section: Subgroup Of Patients With High-grade Agct Characterized By Tsupporting
confidence: 86%
“…Four different major signatures were identified in the tumor samples. Two of the derived signatures were related to normal ageing processes being present in all cells (COSMIC 3, 5, 37 and COSMIC 3, 5, 40, respectively), one to platinum treatment (COSMIC 31,35) and one signature with a yet unestablished cause (COSMIC 4,20,38,45). No signatures related to microsatellite instability (MSI) or homologous recombination (HR) deficiency were detected (see Methods).…”
Section: Mutational Signatures In Agcts Are Related To Ageing and Plamentioning
confidence: 99%
“…Carcinogenesis is a multistep process that can arise from a combination of mutations in oncogenes or tumor suppressor genes or from epigenetic changes in DNA. It is not yet known which of these processes are involved in aGCT, although recent genetic studies of primary and recurrent tumors have identified mutations in the promoter of the TERT gene (coding for telomerase reverse transcriptase), in the KMT2D gene (coding for a histone lysine methyltransferase) and in the TP53 gene [8,14,26]. These mutations' additional contributions to carcinogenesis (along with the FOXL2 mutations and CIN notably described here) have yet to be determined.…”
Section: The Homozygous Foxl2 Genotype In Recurrent Agctsmentioning
confidence: 91%
“…Recently, Fashedemi et al reported on five cases of aGCT with uncommon areas of high-grade morphology. The researchers showed that the TP53 mutation is likely to be involved in high-grade transformation [8]. Molecular markers that could predict recurrence and/or aggressive disease would be a great asset in the management of aGCT.…”
Section: Research Papermentioning
confidence: 99%
“…In the present study, we use adult granulosa cell tumor (AGCT) of ovary and uterine leiomyosarcoma as two application scenarios to test our resolution process. AGCT is a low-grade malignant neoplasm with a signi cant propensity for late recurrence and metastasis 9 . Histologically, granulosa cell tumors (GCTs) divided into adult and juvenile, the former accounted for 95% of all GCTs 9−10 .…”
Section: Methodsmentioning
confidence: 99%